A sustainable trend in COVID-19 research: An environmental perspective - Vadiati, Meysam; Ghasemi, Leyla; Samani, Saeideh; Islam, Md. Aminul; Ahmadi, Arman; Khaleghi, Saeid; Movarej, Maryam; Gorgij, Alireza Docheshmeh; Kisi, Ozgur; Davoodi, Shahla; Dhama, Kuldeep; Tiwari, Ananda; et al. (Frontiers in Environmental Science, 2023)
The COVID-19 pandemic has been the most disrupting phenomenon in this decade. Its potent effects have earned the attention of researchers in different fields around the world. Amongst them, authors from different countries have published numerous research articles based on the environmental concepts of COVID-19. The environment is considered an essential receptor in the COVID-19 pandemic, and it is academically significant to look into publications to follow the pathway of hot subjects and upcoming trends in studies. Reviewing the literature, therefore, can provide valuable information, regarding the strengths and weaknesses of facing the COVID-19 pandemic, considering the environmental viewpoint. The present study categorizes the understanding caused by environmental and COVID-19-related published papers in the Scopus metadata from 2020 to 2021. VOSviewer is a promising bibliometric tool used in the present study to analyze the publications with both “COVID-19*” and “Environment” keywords. Then, a narrative evaluation is utilized to delineate the most interesting research topics. Cooccurrence analysis is applied in this research, which further characterizes different thematic clusters. The published literature mainly focused on four central cluster environmental concepts: air pollution, epidemiology and virus transmission, water and wastewater, and environmental policy. It also reveals that environmental policy has gained worldwide interest with the main keyword “management” and gathers keywords like waste management, sustainability, governance, ecosystem and climate change. Although these keywords could also appear in other environmental policy-related research, the importance of the COVID-19 pandemic requires such comprehensive research. The fourth cluster involves governance and management concerns during the pandemic. Mapping the research topics in different clusters will pave the way for the researchers to view future potential ideas and studies better. The scope for further research needs from the perspective of the environmental concepts is reviewed and recommended, which can expand environmental sciences vital role and value in alerting, observing, and COVID-19 prediction for all four clusters. In another word, the research trend would shift from qualitative studies and perspectives to quantitative ones.